Upaya Peningkatan Kosakata Baku pada Peserta Didik - Wa Ode Irawati; Usman, Fitrawati R.; Suge, Firnawati (Jurusan Ilmu Pendidikan - Universitas Lampung, 2024)
The purpose of this community service is to make efforts to improve the mastery of standard vocabulary for students at Pondok Pesantren Al-Falah Gorontalo.This community service activity uses a mentoring and practice approach. The preparation stages, namely preparation and location survey at the Al-Falah Gorontalo Islamic Boarding School, coordination with the government and the school, preparation of materials, and completion of administration. Furthermore, the implementation procedure is to provide assistance (in the form of explaining standard vocabulary material) to students, applying the crossword puzzle method in standard vocabulary material, and building good relationships with the school. Based on the implementation of the service, it can be seen that students are enthusiastic about finding answers to crossword puzzles. It can be stated that the crossword puzzle method can be used as one of the media in an effort to improve students' vocabulary mastery by being interesting or not boring.